Health and development in BRICS countries - Paulo Marchiori Buss; José Roberto Ferreira; Claudia Hoirisch (Universidade de São Paulo, 2014)
At the beginning of the century, the acronym BRIC first appeared in a study produced by an economist at Goldman Sachs. Economic and financial interest in BRICS resulted from the fact of them being seen as drivers of development. The purpose of this review is to analyze the extent to which what is being proposed at the Declarations of Heads of State and in the Declaration and Communiqué of Ministers of Health of BRICS can provide guidance to the potential of achieving a healthier world. With that in mind, the methodology of analysis of Statements and Communiqué rose from the discussions at the Summit of Heads of State and Ministers of Health was adopted. In the first instance, the study focused on the potential for economic, social and environmental development, and in the second, on the future of health within the group addressed. The conclusion reached was that despite the prospect of continued economic growth of BRICS countries, coupled with plausible proposals for the health sector, strong investment by the countries in S&T and technology transfer within the group, research on the social and economic determinants that drive the occurrence of NCDs - there is the need and the opportunity for joint action of the BRICS in terms of the "diplomacy of health" reinforcing the whole process of sustainable development.